A qualitative study on barriers for the use of respiratory protective devices among rice mill workers in Ampara District, Sri Lanka - K. R. M. Chandrathilaka; Dulani Samaranayake; Kantha Nirmali Lankatilake; Rohini de Alwis Senevirathne; Anuruddha Kumara Karunarathna (College of Community Physicians of Sri Lanka, 2020)
Introduction: Rice milling often carried out in the informal work sector generates paddy dust which is a hazard to the respiratory health of mill workers. Sri Lankan rice mill workers have shown reluctance in using respiratory protective apparatus during rice milling.   Objectives: To describe the barriers for the use of respiratory protective devices during rice milling   Methods: A qualitative study was conducted in the divisions of Ampara and Uhana in Ampara District in Sri Lanka during February 2016. Twenty-two in-depth interviews were conducted among rice mill workers, health professionals and government officers related to rice milling industry. Data were analysed using content analysis method.   Results: The rice mill workers' non-use of respiratory protective methods was mainly due to their negligence in personal respiratory health care and lack of support from the employer, health care institutes and other related institutes. Low level of comprehension of workers and less manpower in health care and other institutions were other contributing factors.   Conclusions: Low priority given for respiratory health care by the workers, poor work environment and less support from the mill owner and relevant government authorities have resulted in non-use of respiratory protective devices among rice mill workers. Improving unhealthy work behaviour such as non-use of respiratory protective devices of the informal work sector is recommended using industry-based health education programs.